In vitro antiproliferative and antioxidant activity of three fungal strains from the White sea - Couttolenc, Alan; Padrón, José M.; Shnyreva, Alla V.; Sergeeva, Albina I.; Kurakov, Alexander V.; Trigos, Ángel (Polar Science, 2021)
Fungi have been recognized as a prolific source of bioactive compounds with a wide spectrum of bioactivities, nevertheless, the information about marine polar fungi is scarce. Due to this fact, the purpose of this study was to investigate the antiproliferative activity and antioxidant capacity of the extracts of three fungal strains isolated from the White Sea (Coprinellus diseminatus, Simplicillium lamellicola and Akanthomyces muscarius). The antiproliferative activity test was carried out by the SRB method and the cell lines tested were A549, HBL-100, HeLa, SW1573, T-47D and WiDr. The antioxidant capacity was measured employing the ABTS and galvinoxyl methods. The strain that showed the most antiproliferative activity was A. muscarius; it demonstrated activity in all the extracts tested, at least against two of the six tested cell lines, also the biomass ethanolic extract and the culture broth ethyl acetate extract of Coprinellus diseminatus showed antiproliferative activity against some of the tested cell lines. In the antioxidant capacity test, the ethyl acetate extracts of the culture broth of the three strains showed more activity. This indicates that arctic marine-derived fungi are capable to produce bioactive metabolites with antiproliferative activity and antioxidant capacity, comparable to other marine-derived fungi, and in some cases even more active than known medicinal mushrooms. journal article